Assyrian Attitude Towards Captive Enemies: A 2700‐year‐old Paleo‐forensic Study. (16th November 2012) - Cohen, H.; Slon, V.; Barash, A.; May, H.; Medlej, B.; Hershkovitz, I.
Abstract The Assyrians, who ruled at the height of their power between Egypt and the Persian Gulf (745–630 BC), are known from historical records to have been cruel and unrelenting towards their enemies. However, osteological evidence for this behavior is scarce. We herein present a case of an adult male skeleton, dated to the Iron Age IIB period (second half of the 8th century BC), who manifests traumatic injuries to the skull, left forearm, vertebrae, and ribs. Using modern forensic methods, the injuries were studied, and the consequences that led to these injuries reconstructed. Three possible scenarios are presented: (i) wounds inflicted during a chaotic battle; (ii) wounds caused by the chasing and capturing of a victim; and (iii) a commonly practiced violent attitude of Assyrian soldiers towards a captive combatant. Combining all the evidence at hand, the latter scenario appears more likely. This skeleton may therefore be one of the sole tangible physical evidence for the veracity of the Assyrians' post‐battle behavior, as depicted in ancient texts and reliefs. Copyright © 2012 John Wiley & Sons, Ltd.